1987
DOI: 10.1029/ja092ia07p07487
|View full text |Cite
|
Sign up to set email alerts
|

The role of ring current O+ in the formation of stable auroral red arcs

Abstract: Coulomb collisions between ring current protons and thermal electrons were first proposed by Cole (1965) as the energy source for stable auroral red (SAR) arcs. Recent observations have shown that the ring current and magnetospheric plasma contain significant amounts of heavy ions (Johnson et al., 1977; Young et al., 1977; Geiss et al., 1978; and others). In fact, the ring current is often dominated by heavy ions at those energies (E ≤ 17 keV) important for Coulomb collisions on SAR arc field lines (Kozyra et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
113
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 20 publications
(16 reference statements)
10
113
1
Order By: Relevance
“…Furthermore, the total energy, contained in the ring current particles, which is of the order of 1023 erg, is sufficiently large to cause appreciable atmosphere ionization or heating if released in a short time. Many effects, like subauroral electron temperature enhancements [Brace et al, 1967], stable auroral red arcs (SAR) [Kozyra et al, 1987[Kozyra et al, , 1997 and energetic neutral and ion precipitating fluxes [Dessler et al, 1961], are observed at midlatitudes as consequences of this energy release. Moreover, the ring current can also act as an energy source contributing to plasma instabilities and wave growth.…”
Section: Paper Number 1999ja900310mentioning
confidence: 99%
“…Furthermore, the total energy, contained in the ring current particles, which is of the order of 1023 erg, is sufficiently large to cause appreciable atmosphere ionization or heating if released in a short time. Many effects, like subauroral electron temperature enhancements [Brace et al, 1967], stable auroral red arcs (SAR) [Kozyra et al, 1987[Kozyra et al, , 1997 and energetic neutral and ion precipitating fluxes [Dessler et al, 1961], are observed at midlatitudes as consequences of this energy release. Moreover, the ring current can also act as an energy source contributing to plasma instabilities and wave growth.…”
Section: Paper Number 1999ja900310mentioning
confidence: 99%
“…The rate of energy transfer from the energetic ringcurrent ions to plasmaspheric electrons due to Coulomb collisions has been discussed extensively by Kozyra et al (1987). There is no information available on the ringcurrent population for this storm, and we are therefore forced to assume a heating rate function.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…(A10) of the Appendix. At the present time, waveparticle interactions (Thorne and Horne, 1992;Erlandson et al, 1993;Horne and Thorne, 1993) and Coulomb collisions between ring-current ions (Cole, 1965;Kozyra et al, 1987;Slater et al, 1987;Kozyra and Nagy, 1991;Fok et al, 1995aFok et al, ,b, 1993 and plasmaspheric electrons and ions are the most plausible mechanisms used to explain electron temperature enhancements and the associated SAR arcs. The present work addresses the contribution from this latter process.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations